Servqual analysis in improving customer satisfaction at PT Joie Production Bandung - Mulyani, Lenny; Sibarani, Mentiana (Indonesian Journal of Multidisciplinary Science, 2024)
The purpose of this study is to examine the influence of service quality on consumer satisfaction at PT Joie Production, a convection company located in the city of Bandung, Indonesia. The study uses probability sampling with a simple random sampling method, and the sample size is determined using the Slovin formula which produced 58 respondents from a population of 140 consumers in the past year. The data was analyzed using statistical methods to test the validity and reliability of the questionnaire, as well as measure the quality of service based on the SERVQUAL method. The results of the study show that the overall service quality has a negative average gap of -0.022, indicating that services are generally below customer expectations and unsatisfactory. The highest perception value was in the responsivity dimension of 4.41 and the lowest perception value is reliability of 3,899. Based on the results of interviews with several consumers, it was obtained that price is a consideration, but from the waiting time can be an important thing and the reason why consumers do not continue PT. When complaints are handled properly, customers are more likely to return to transact again, creating stronger loyalty Complaints that are handled well, along with quality service, can significantly increase customer satisfaction levels.